1999
DOI: 10.1089/107999099313686
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Innate and Acquired Antitumor Immunity by Bystander gamma delta and alpha beta T Lymphocytes with Th2 or Tr1 Cytokine Profiles

Abstract: It has been thought that natural killer (NK) cells appearing early in tumor lesions play a pivotal role in the innate immunity against tumor cells. Although NK cells serve as the first tumoricidal effector cells, they subsequently promote a shift in effectors from themselves to tumor-specific cytotoxic T lymphocytes (CTLs) that mediate the acquired immunity. The mechanism of this shift has not been fully elucidated, however, NK cell-derived T helper (Th) 1 cytokines such as interferon (IFN)-gamma seem to play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…The clinical significance of immune modulation during cancer is supported in several ways. High levels of NKCA in cancer patients correlate with a good prognosis (Gonzales, et al, 1998;Koda, et al, 1997;Liljefors, et al, 2003;Nakamura, et al, 2000;Seo and Tokura, 1999;Taketomi, et al, 1998). Impaired NKCA correlates with invasiveness of human malignancy (Levy, et al, 1984) and reduced NKCA is a significant prognostic indicator of lymphatic involvement, serosal invasion, lymph node metastatic disease and a poorer survival rate (Takeuchi, et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of immune modulation during cancer is supported in several ways. High levels of NKCA in cancer patients correlate with a good prognosis (Gonzales, et al, 1998;Koda, et al, 1997;Liljefors, et al, 2003;Nakamura, et al, 2000;Seo and Tokura, 1999;Taketomi, et al, 1998). Impaired NKCA correlates with invasiveness of human malignancy (Levy, et al, 1984) and reduced NKCA is a significant prognostic indicator of lymphatic involvement, serosal invasion, lymph node metastatic disease and a poorer survival rate (Takeuchi, et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…23,48,54 Hodgkin cells also secrete the chemokine TARC, which specifically recruits IL-4-secreting Th2 cells, and a Th2 growth factor, IL-13. [55][56][57][58] Both favor the creation of a noncytotoxic Th2 environment. Although this is a daunting list of evasion mechanisms, their very profligacy argues that multiple defenses are required to protect the tumor cells from attack.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have suggested that the immunosuppressive function of ␥␦ T cells is mediated mainly by cytokines (42,45). Because ACAID is a Th2-like phenomenon with an immunosuppressive consequence, we hypothesized that ␥␦ T cells need to secrete Th2 cytokines (such as IL-10 and IL-4) for the generation of efferent Tregs and down-regulation of DTH.…”
Section: ␥␦ T Cells Must Produce Il-10 To Induce Acaidmentioning
confidence: 97%